DEVELOPMENT OF DIGITAL CALISTUNG GAME LEARNING MEDIA FOR EARLY CHILDHOOD - Rusmono, Evi Selva Nirwana, Yufiarti (International Journal of Advanced Science and Technology, 2020)
This article aims to develop media learning games calistung digital for early childhood. The study is using a combination of research models and educational development approaches used is a model system designed by Walter Dick and Lou Carey and development tools software game calistung digital by using a model of the cycle of life from Parekh.  The research method uses the R&D method in Borg and Gall which adopts the Dick and Carey model. The product testing phase begins with a material expert, a learning design expert, a learning media expert, and a multimedia expert. Then the products are tested to several children of age early, namely three people's evaluation of the individual, six people for the evaluation of the group of small and ten people to evaluate the group greatly. The results of the study showed the value of expert material is very good, the value of the expert design of learning is very good, the value of expert media of learning is very good, and the value of expert multimedia either. According to the expert, the material aspects of the assessment on (a) Compliance with learning objectives, (b) Simplicity, (c) Elements of message design, (d) Organizing materials, (e) Instructions for how to use are very good. According to the learning design aspects of assessment (a) instructional objectives, (b) Learning Outcomes Assessment Tools, (c) Developing Instructional Strategies, (d) Instructional Media is very good. According to the expert media learning as aspects of the visual / performance/quality technical, namely : (1) setting among others, (a) alignment, (b) the form, c) the rules of a third, (d) closeness, (e) the steering, (f) the contrast figure - setting; (2) consistency, (3) Balance, (4) Color, (5) Ease of reading, (6) Interest element of text/graphics/component accessory (1) Style letters, (2) size, (3) spaces, (4 ) colors, (5) the use of the letter big own following the principles of designing media learning.  According to multimedia experts that (1) text, (2) images, (3) sound, (4) animation is following the principles of multimedia development is good. Then it can be concluded that digital calistung game learning media is appropriate to be used in learning.